Assessment of dyspneic sensation in patients with type 2 diabetes - Mizab, Chadia; Sánchez, Enric; Gutiérrez-Carrasquilla, Liliana; Balsells, Núria; Arqué, Anaïs; Ruano, Raquel; Mateu, Magda; Zorzano-Martínez, Marta; Pomés, Anna; García-Aguilera, Esther; Martí, Raquel; Manzanares, José María; et al. (Frontiers in Endocrinology, 2023)
Introduction: Individuals with type 2 diabetes (T2D) should be considered a susceptible group for pulmonary dysfunction. So, we aimed to evaluate the sensation of breathlessness in this population by administering two well-validated questionnaires. Methods: This is a cross-sectional study with 592 people without known respiratory disease (353 with T2D) who answered the modified Medical Research Council (mMRC) questionnaire. In addition, 47% also responded to the St George Respiratory Questionnaire, a specific instrument designed to be applied to patients with obstructive airway disease. Results: Patients with T2D showed a higher mMRC score in comparison to the control group [1.0 (0.0 – 4.0) vs. 0.0 (0.0 – 4.0), p<0.001]. A higher prevalence of subjects with mMRC ≥2 was observed in T2D that in the control group (20.2% vs. 11.6%, p=0.004). Participants with T2D and mMRC ≥2 showed a higher HbA1c (8.2±1.6% vs. 7.8±1.6%, p=0.048), longer T2D evolution and higher prevalence of nephropathy. In the multivariate analysis, the presence of T2D [OR=1.95 (1.19 to 3.22), p=0.008] in all the population, and HbA1c [OR=1.19 (1.01 to 1.41), p=0.034] and the presence of diabetic nephropathy [OR=2.00 (1.14 to 3.52), p=0.015] in patients with T2D, predicted a mMRC ≥2. Finally, no differences were observed regarding the SGRQ score among groups. Conclusions: Patients with T2D showed a greater sensation of dyspnea than subjects with normal carbohydrate metabolism. Risk factors included poor metabolic control and the presence of renal disease.